Morpho-Histology, Endogenous Hormone Dynamics, and Transcriptome Profiling in Dacrydium Pectinatum during Male Cone Development - Wenju Lu (MDPI AG, 2021)
Dacrydium pectinatum de Laubenfels is a perennial gymnosperm species dominant in tropical montane rain forests. Due to severe damages by excessive deforestation, typhoons, and other external forces, the population of the species has been significantly reduced. Furthermore, its natural regeneration is poor. To better understand the male cone development in D. pectinatum, we examined the morphological and anatomical changes, analyzed the endogenous hormone dynamics, and profiled gene expression. The morpho-histological observations suggest that the development of D. pectinatum male cone can be largely divided into four stages: microspore primordium formation (April to May), microspore sac and pollen mother cell formation (July to November), pollen mother cell division (January), and pollen grain formation (February). The levels of gibberellins (GA), auxin (IAA), abscisic Acid (ABA), cytokinin (CTK), and jasmonic acid (JA) fluctuated during the process of male cone development. The first transcriptome database for a Dacrydium species was generated, revealing >70,000 unigene sequences. Differential expression analyses revealed several floral and hormone biosynthesis and signal transduction genes that could be critical for male cone development. Our study provides new insights on the cone development in D. pectinatum and the foundation for male cone induction with hormones and studies of factors contributing to the species’ low rate of seed germination.